2021
DOI: 10.1111/ppc.12797
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of resilience in the relationship between peer pressure and risky behaviors among nursing students

Abstract: Purpose: To examine the moderating role of resilience in the relationship between peer pressure and risky behaviors among nursing students. Design and Methods:A cross-sectional correlational study carried out with 512 students. Findings:The mean age was 20.90 ± 1.66. Of the students, 82.4% were females 99.0% were single, 71.5% had moderate socioeconomic status. While peer pressure directly made an effect on whole subdimensions for risky behaviors (p < 0.001), resilience had an effect on antisocial behavior, dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…However, in the studies conducted with university students, inconsistent results were reported in terms of the relationship between income status and psychological resilience. While socioeconomic status affected the resilience in some studies (Çiydem, 2017), it did not affect the resilience in others (Kong et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, in the studies conducted with university students, inconsistent results were reported in terms of the relationship between income status and psychological resilience. While socioeconomic status affected the resilience in some studies (Çiydem, 2017), it did not affect the resilience in others (Kong et al, 2016).…”
Section: Discussionmentioning
confidence: 93%
“…In the study, the mean ARS score of the female students was significantly higher than that of the male students. Although women are included in psychologically at‐risk groups due to specific issues such as menstruation, pregnancy, childbirth, and the risk of domestic violence, it has been generally stated that women are more resilient than men (Çiydem, 2017; Güngörmüş et al, 2015). However, only some of the studies showed that gender affected resilience (Yiğitbaş et al, 2018), while other studies reported that it did not (Antúnez et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies used a varying composite measure of suicidal thoughts and behaviours (Aradilla‐Herrero et al., 2014; Ciydem & Bilgin, 2021; Divya et al., 2022; Leal & Santos, 2016; López‐Narváez et al., 2020; Moraes et al., 2021; Poreddi et al., 2021; Quarshie et al., 2019; Uğurlu & Ona, 2009). Regarding prevalence, one study found no difference in occurrence of suicidal behaviours in nursing students compared with that in medical students (10.3% vs. 11.6%, respectively p = .73) (López‐Narváez et al., 2020), and another found that students nurses had a lower suicide probability score than students training to be ‘health officers’ (mean Suicide Probability Scale score 65.96 [19.22] vs. 73.16 [21.65], p < .05) (Uğurlu & Ona, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Experience of peer pressure, and lower levels of resilience was found to be associated with suicidal tendency among nursing students in Turkey. However, moderator analysis examining whether resilience moderated the relationship between peer pressure and suicidal tendency was not significant (Ciydem & Bilgin, 2021). Finally, no evidence was found between attitudes towards suicide and experiences of suicidal thoughts or behaviours among students in India (Poreddi et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of resilience theory, a higher resilient level may be linked to a greater capacity for planning, guiding, and monitoring one’s behavior flexibly in the face of changing circumstances (Campbell-Sills et al, 2006). An examination revealed that students who reported high levels of resilience during university education are less prone to exhibit risky behaviors (Ciydem & Bilgin, 2021). Risk-taking for young adults include smoking, alcohol and substance use, dropping out, poor eating habits, suicidal tendencies, and antisocial behaviors (Genctanirim, 2014).…”
Section: Introductionmentioning
confidence: 99%